Identification of psychological constructs for a positive psychology intervention to assist with the adjustment to closed loop technology among adolescents living with type 1 diabetes - Kruger, Sylvia; Deacon, Elmari; van Rensburg, Esmé; Segal, David (Frontiers in Psychology, 2023)
Aim: Adolescents have been identified as the group who struggle most with successful adjustment to closed loop technology. This study aims to identify the psychological constructs that should form part of a positive psychology intervention to assist with the adjustment to closed loop technology among adolescents living with type 1 diabetes. Method: Qualitative document analysis was employed to integrate findings from two documents: a published ongoing intervention study and a recent phenomenological study by the authors. Reflexive thematic analysis was used to identify themes from the documents. Findings: The following themes were identified as important psychological constructs that aid adjustment: the importance of knowledge and education; the process of positive adjustment to closed loop technology; a positive outlook; and building a relationship with diabetes. Conclusion: Interventions are needed to assist adolescents in their adjustment to closed loop technology. The psychological constructs identified served as a starting point in designing an effective, evidence-based intervention grounded in data and theory. Knowledge and education, responsibility, identity, positive affect, gratitude, support, and trust are psychological constructs that need to be included in an intervention program.